Visibility and representation of women in multiple sclerosis research - Thomson, Alison (Neurology, 2019)
OBJECTIVE: To establish the gender distribution of multiple sclerosis (MS) researchers across high-impact neurologic publications, MS-specific journals, and the European Committee for Treatment and Research in MS (ECTRIMS). METHODS: Journal editorial boards and contents were retrieved online to assess first-named and senior authors. Published tables of contents for each journal from 2017 were reviewed. Congrex, the ECTRIMS organizers, were contacted and speaker names were obtained from online abstracts to assess visible opinion leaders. RESULTS: A total of 2,080 articles were analyzed across 4 general neurology journals, and 452 across 2 MS journals. Overall, 36% of general neurology articles had a female first name author and 25% had a female senior author. In MS-specific journals, 44% of first authors and 35% of senior authors were female, with similar proportions of unique authors. There is limited female representation on the ECTRIMS executive board, but reasonable balance on Council. Almost 50% of attendees in 2017 were female, but only 35% of invited speakers. CONCLUSIONS: There is substantial female drop-off between junior and senior research level across multiple areas. Strategies to support gender balance are urgently required, including developing mentorship schemes, ensuring gender balance in conferences, and thorough examination of the barriers facing female academics with direct challenges to address unconscious bias.